The unnatural realism of Borges - Hong, Yuchen (Nanyang Technological University, 2020)
Critics of Borges's short stories have mostly pointed towards the writer's predisposition towards creating complex, labyrinthine worlds; such a view has grounded him firmly as a writer of magic realism or an early postmodernist. A smaller subset of critics has pointed out the coincidence of his stories with 20th century scientific concepts, and that his fictions relate in a meaningful and even technical way to reality. I argue that both sides of the critical spectrum surrounding Borges are equally valid – and that, given the shocking nature of some of the 20th century's most important scientific revelations that betray the labyrinthine and indeterminate nature of reality, I contemplate whether or not Borges's stories are instead a form of realism, albeit a particularly avant-garde one. I propose that Borges's short stories also function as serious thought experiments that illustrate the counter-intuitive nature of the reality that we see and interact with on an everyday basis. He points out, within his fiction, that the natural and the unnatural are really two sides of the same coin. My thesis provides an account of Borges's narrative method using the term “unnatural realism,” in order to justify the writer's attempt to embody reality in a way that does justice to 20th century science – which ironically involves the use of intricate labyrinths and logical paradoxes, techniques that fall under the category of unnatural narrative.